Filipiniana as a clothing concept for three Filipino designing women Patis Tesoro, Malu Veloso and Dita Sandico-Ong - Del Rosario, Anilyn T.; Elumba, Patricia Santos (2003.)
This thesis is a descriptive study of how three Filipino designing women - Patis Tesoro, Malu Veloso and Dita Sandico-Ong view and interpret Filipiniana as a clothing concept. This study focused on Filipiniana as a clothing concept from the point of view of three designing women. It discussed the three designers' definition of Filipiniana as a clothing concept, their design influences, and the techniques that they employ in making their creations. The researcher utilized the descriptive method in conducting this study. She conducted intensive interviews with the three designers to learn about their Filipiniana design concepts. To complement the interviews, the researcher did an intensive examination and comparison of the three designers' techniques in creating their kind of fashion. The results of this study revealed that all three designers believe that local craftsmanship is the single most important element of Filipiniana wear. Though Patis, Malu and Dita have a lot in common in terms of their beliefs on the core elements of Filipiniana, they have achieved varied looks in their designs through their unique way of employing various techniques on the clothes that they create. Patis Tesoro, Malu Veloso and Dita Sandico-Ong combine their respective career backgrounds, influences, techniques, markets and missions to form their own unique Filipiniana concept. Their individual concepts, in return, become a part of the continuous growth of Filipiniana as a clothing concept.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Costume design -- Philippines; Costume designers -- Philippines